Feasibility and acceptability of MyWarung©: a food poisoning prevention smartphone-apps during dining out - Zaujan, Nur Afifah Mursyida; Ali, Asma'; Misni, Norashiqin; Osman, Malina; Chee, Hui Yee; Ithnin, Nur Raihana; Sukeri, Surianti; Chin, Christie Pei Yee (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2021)
Introduction: Eating out has always been associated with increasing cases of food poisoning. These problems can be minimized through mobile applications and technology development. A mobile application called MyWarung© was developed to provide an alternative, improved tool for improving food poisoning knowledge and preventive behaviour. Methods: This cross-sectional study aims to assess the feasibility and acceptance of the MyWarung© application for consumers in Terengganu. The 50 consumers were selected based on the inclusion and exclusion criteria using convenience non-probability sampling. The data were collected through a questionnaire that included three components: socio-demographic, feasible (6 components) and acceptable (7 components). The scoring above 80.0% indicates an acceptable, while lower than 80.0% show unacceptable for both feasibility and acceptability sections. SPSS 22.0 has analyzed the data. Results: The results showed excellent feasibility with a median score of 27.5 (IQR 6.0) out of 30.0, and acceptance with 32.0 (IQR 7.0) out of 35.0. Majority of the respondents agreed that the app is easy to use (94.0%), easy to understand (88.0%), attractive (84.0%), catchy (88.0%), provides more information (96.0%), efficient (96.0%), knowledge improvement (96.0%), beneficial (100.0%), useful application (88.0%), and recommend to the other people (84.0%). The overall result showed that most respondents agreed that MyWarung© application was feasible and acceptable with 90.0% and 86.0% feasibility and acceptability rate. Conclusion: The MyWarung© application among consumers can be highly feasible and acceptable in preventing food poisoning during dining out.